K-Pop Fandom and Beauty Trends: Investigating the Engagement of Young Urban Indian Women with BTS - Bhaisaheb, Fatema; Shendurnikar, Nidhi (Bodhi: An Interdisciplinary Journal, 2024)
The Korean wave (Hallyu) has emerged as a global phenomenon spreading to many countries including India since the nineties. In the initial phase, Korean dramas attracted international attention, after which Korean pop music took the world by storm. With the rising popularity of K-pop in India (Jiju, 2023), it is essential to understand the influence it carries on Indian fans. This paper delves into understanding how K-Pop has influenced ideas about beauty among young adults in Vadodara, a cosmopolitan town located in the western Indian state of Gujarat. Three focus group discussions were carried out with fifteen youngsters who identified as K-pop fans, particularly of BTS (Bangtan Boys), a South Korean boy band formed in 2013. The research design adopted for this study was qualitative and exploratory. Theoretical underpinnings informed by The Social Construction of Reality (Berger & Luckman,1966) and The Juggernaut of Modernity (Giddens, 1990) were used to examine the influence of K-Pop consumption on ideas about beauty in the context of fandom culture. The findings reveal no significant influence on beauty-related values and ideals. However, K-pop does have a positive bearing on other aspects of the lives of its fans such as challenging stereotypes, promoting self-love, addressing social problems, and positive impact on individual personality. In addition, a shift in fashion ideals is observed indicating a growing trend of Korean-inspired fashion trends.